Anaplasma platys and Rickettsia massiliae in Rhipicephalus sanguineus sensu stricto ticks collected on dogs in the Patagonian region of Argentina - Maas, Lara M. I. (2024)
The aim of this study was to examine the presence of tick-borne rickettsial bacteria inRhipicephalus sanguineus sensu stricto ticks collected from dogs in the Patagonian regionof Argentina. Fourteen stray dogs from Valcheta, Río Negro province, Argentina were examinedfor the presence of R. sanguineus s.s. ticks. Ninety ticks were collected and identified tospecies level. DNA was extracted and analysed by conventional PCR assays for the presence oftick-borne bacteria belonging to the genera Anaplasma, Ehrlichia and Rickettsia. Thirty-threetick pools were tested by different PCR assays of which 3 were positive for Anaplasmataceaebacteria. From the 3 Anaplasmataceae positive samples, 2 partial 16S rDNA sequences weregenerated and belonging to Anaplasma platys, the causative agent of canine cyclic thrombocytopenia.Two tick samples were positive in Rickettsia specific PCR assays and were identifiedby phylogenetic analysis as Rickettsia massiliae, a member of the spotted fever group rickettsiae.The results of this study demonstrate the molecular detection of 2 rickettsial bacteria inR. sanguineus s.s. in a region of Argentina where no data were available so far.